1988
DOI: 10.1590/s0006-87051988000100002
|View full text |Cite
|
Sign up to set email alerts
|

Deficiência hídrica simulada nos diferentes estádios de desenvolvimento de um cultivar precoce de soja

Abstract: Estudou-se o efeito da deficiência hídrica em diferentes estádios do cultivar precoce de soja Paraná. As plantas foram cultivadas em casa de vegetação, em solução nutritiva de Hoagland. A deficiência hídrica foi simulada pela adição de polietilenoglicol (PEG) 6% na solução nutritiva, nos seguintes estádios: vegetativo, florescimento e enchimento do grão. Os resultados mostraram que: (1) a deficiência hídrica nos três estádios diminuiu a produção e o número de vagens e de grãos em relação à testemunha; (2) no p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…However, among plants submitted to drought stress at the reproductive stage, grain yield was significantly lower than was the case of plants under water deficit induced at the vegetative stage under either natural conditions or irrigation. Thus, water withholding at the reproductive stage was more harmful to soybean production, as has also been reported by several authors in studies evaluating soybean plants submitted to different water availability levels (Nogueira and Nagai 1988;de Paiva Rolla et al 2014;Carvalho et al 2015;Crusiol et al 2017).…”
Section: Canopy Temperature and Nrctsupporting
confidence: 73%
“…However, among plants submitted to drought stress at the reproductive stage, grain yield was significantly lower than was the case of plants under water deficit induced at the vegetative stage under either natural conditions or irrigation. Thus, water withholding at the reproductive stage was more harmful to soybean production, as has also been reported by several authors in studies evaluating soybean plants submitted to different water availability levels (Nogueira and Nagai 1988;de Paiva Rolla et al 2014;Carvalho et al 2015;Crusiol et al 2017).…”
Section: Canopy Temperature and Nrctsupporting
confidence: 73%
“…This result may be related to a trait inherited from one of their parents. Nogueira et al (2015), working with cultivar Packham's Triumph, detected 12 anthers per flower. Cultivars Seleta and Tenra showed a small number of pollen grains per anther and per flower.…”
Section: Number Of Anthers Per Flower and Pollen Grains Per Anther Anmentioning
confidence: 99%
“…In turn, soybean plants subjected to water deficit during the vegetative stages presented grain yield similar to plants under natural rainfall (NIRR treatment), demonstrating that the water deprivation during reproductive stages is more harmful to soybean crop. Several authors have reported similar values of soybean yield on plants under water deficit during the vegetative stages (and rain watered during reproductive stages) compared to plants under good conditions of water availability [49][50][51][52].…”
Section: Effect Of Experimental Treatments On Climatic Water Balance Soil Moisture Grain Yield and Leaf Reflectancementioning
confidence: 89%